Short Communication: Effects of black soy phytoestrogens (Glycine soja) on elevated levels of estradiol in rat blood (Rattus novergicus) ovariectomy - Dwi Yuliawati; WURI WIDI ASTUTI; FITRI YUNIARTI (Nusantara Bioscience, 2020)
Abstract. Yuliawati D, Astuti WW, Yuniarti F. 2020. Effects of Black Soy phytoestrogens (Glycine soja) on elevated levels of estradiol in Rat Blood (Rattus norvegicus) ovariectomy. Nusantara Bioscience 12: 55-58. Menopause is the transition from productive to non-productive times due to reduced estrogen and progesterone and has an impact on improving cardiovascular problems. The fulfillment of estrogen needs in menopause can use a type of phytoestrogens from black soybeans. The purpose of research is to prove the administration of black soy extract (Glycine soja) can increase the levels of estradiol in the rat blood (Rattus norvegicus) ovariectomy. Design research uses post-test only control group design. Twenty-five female rats were randomly divided into 5 groups (n = 5 tails per group), negative controls, positive and 3 treatments. Ovariectomy was performed in a group of positive controls and treatment. Thirty-day post ovariectomy rats were given appropriate group treatment (negative control, positive, and treatment with the administration of black soy extract dose of 50, 100, 150 mg/200  g/day for 30 days). The estradiol test used the Enzyme-linked immunosorbent assay (ELISA). Anova's test results with a significant degree of ? = 0.05 established that the p-value of 0.000 was less than ? = 0.05, meaning there was a significant effect of giving black soy extract on increased levels of estradiol in the rat blood ovariectomy. Post - Hoc Tukey testing shows increased the highest estradiol levels in the dose treatment group 100 mg/200  g/day. This research proves that the administration of black soy extract (Glycine soja) can increase the levels of estradiol in the rat blood (Rattus norvegicus) ovariectomy.